Beyond representation? A material-ecocritical reading of Derek Mahon’s “eco-poetry” - Catherine CONAN (E-REA)
This article reads Derek Mahon’s latest collection of poems, Against the Clock (2018) through a theoretical framework inspired by flat ontologies, notably agential realism and object-oriented ontology. Critics of the Irish poet have noted a turn towards greater environmental awareness since the publication of Harbour Lights (2005). This is evidenced notably by his poetic representation of various ecological crises, local or global, as well as references to key figures of the environmental movement such as Rachel Carson or Naomi Klein, so that Mahon has been dubbed an “eco-poet”. The appellation suggests that ecopoetry is endowed with actual effectiveness in the material world by acting upon its readers’ minds. I offer a critical analysis of such claims in the specific case of Mahon’s poetry by gathering environmental emergency, poems and readers on the same ontological plane as objects. This makes it possible to study their interobjective relations without isolating the speaking and representing mind from the represented endangered world. Crucial to this discussion is an examination of metaphor, which beyond representation generates a sensory engagement with the material reality described in the poems.